(untitled) (Journal of Global Accounting, 2024)
This article evaluated the effect of outlook and resource allocation disclosures on the market price per share (MKPF) of listed banks in Nigeria. The research design was ex post facto and simple linear regression was used to analyse the data obtained from five (5) banks to determine how these elements of integrated reporting influence investor decisions measured by the market price per share. The findings reveal that while resource allocation strategies (RAS) do not significantly affect MKPF, outlook disclosures (OD) show a marginally significant negative effect. The study underscores the need for banks to refine their disclosure practices, particularly in providing more detailed outlook information, and suggests that regulators should consider enforcing stronger guidelines for these disclosures to enhance market transparency and investor confidence.